Sosialisasi Inovasi Beton Ramah Lingkungan Berbasis Tempurung Kelapa sebagai Substitusi Agregat Kasar - Rifaldi Adi Saputra; Era Agita Kabdiyono; Agung Sakti Meldian; Stevi Cahyani; Yayo Hardiansah; Galang Romadlon; Hariyadi Hariyadi (Asosiasi Dosen Muda Indonesia, 2026)
The increasing use of concrete in infrastructure development has led to a growing demand for natural aggregates, particularly gravel as coarse aggregate. This condition requires the introduction of environmentally friendly alternative materials based on local resources. Coconut shell is an organic waste commonly found in communities, yet its practical use as a construction material remains limited. This community service activity aims to improve participants’ knowledge and basic skills in utilizing coconut shell as a substitute for coarse aggregate in environmentally friendly concrete mixtures. This study employed a descriptive qualitative method through socialization, demonstration, simple practice, observation, documentation, discussion, and evaluation of participants’ understanding. The data were analyzed descriptively to explain the implementation process, participants’ responses, and changes in their understanding of coconut shell waste utilization. The results show that participants gained knowledge about the concept of green concrete, the function of coarse aggregate in concrete mixtures, the initial processing stages of coconut shell, and the potential of local waste as an alternative material for simple construction applications. The implication of this activity is the improvement of community awareness regarding waste utilization and the importance of sustainable construction materials. The originality of this activity lies in its educational and practical approach to introducing coconut shell as a coarse aggregate substitute through direct socialization and hands-on practice with the community.